Water Quality Monitoring System Using Server IOT (Internet of Things) and Sensor - Purno Wahyu, Ari (International Journal of Psychosocial Rehabilitation, 2020)
This research discusses the implementation of the Smart Farming System in hydroponic plantations that utilize remote data communication via the internet. In hydroponic plantations, a control algorithm is programmed on the Arduino Uno micro controller with a pH meter and EC meter as measurement variables, as well as pumped water discharge rates and fertilizer doses as control variables. To monitor all control conditions using a website-based information system was developed with a PHP programming language framework, namely CodeIgniter, and MySQL as a database. This web server can be accessed by operators who are far from the plantation to monitor process variables and change set points. This web server is realized based on the concept of the Internet of Things and uses the Ethernet Shield communication module and the Hypertext Transfer Protocol (HTTP) communication protocol.